Pseudopodium-enriched atypical kinase 1 regulates the cytoskeleton and cancer progression - Wang, Yingchun (National Academy of Sciences, 2010)
Regulation of the actin-myosin cytoskeleton plays a central role in cell migration and cancer progression. Here, we report the discovery of a cytoskeleton-associated kinase, pseudopodium-enriched atypical kinase 1 (PEAK1). PEAK1 is a 190-kDa nonreceptor tyrosine kinase that localizes to actin filaments and focal adhesions. PEAK1 undergoes Src-induced tyrosine phosphorylation, regulates the p130Cas-Crk-paxillin and Erk signaling pathways, and operates downstream of integrin and epidermal growth factor receptors (EGFR) to control cell spreading, migration, and proliferation. Perturbation of PEAK1 levels in cancer cells alters anchorage-independent growth and tumor progression in mice. Notably, primary and metastatic samples from colon cancer patients display amplified PEAK1 levels in 81% of the cases. Our findings indicate that PEAK1 is an important cytoskeletal regulatory kinase and possible target for anticancer therapy.